Obstacles to global implementation of CAR T cell therapy in myeloma and lymphoma - Medina-Olivares, Fernando J.; Gómez-De León, Andrés; Ghosh, Nilanjan (Frontiers in Oncology, 2024)
Chimeric Antigen Receptor T-cell (CAR-T) therapies are transforming the treatment of B-cell lymphoma and myeloma, yet global access challenges and barriers for their implementation persist. Global access disparities persist, particularly for persons living in low and middle-income countries and for underserved populations in high income countries. In this review we address patient-related factors including age, comorbidities, fitness, race and ethnicity, and geographic location for CAR-T access. Also, we review disease-related and health system barriers like disease biology, potential for short and long-term toxicity, insurance access, referrals, supply and manufacturing, regulation, costs and treatment center capacity. Lastly, alternatives for overcoming these barriers exemplified by research efforts worldwide are discussed, emphasizing the need for a multifaceted approach from all stakeholders to improve global accessibility and ensure equitable access and improved outcomes for patients worldwide. Chimeric antigen receptor T-cell therapies have revolutionized the management of persons with relapsed/refractory B-cell lymphoma (1) The first generation of CAR-T cells were not clinically effective due to low persistence (2) Subsequently, the emergence of second-generation CAR-T cells designed to target the antigen CD19 with CD28 or 4-1BB costimulatory domains coupled with CD3 ζ improved CAR T cell in vivo persistence and efficacy, leading to their establishment as a novel treatment modality for patients with B-cell non-Hodgkin Lymphomas (3) In 2013, reports of CAR T-cell therapies directed against the B-cell maturation antigen (BCMA) aimed for persons with multiple myeloma (MM) emerged. Since 2017, six CAR T products have been approved for various indications in relapsed or refractory B cell non-Hodgkin lymphoma or multiple myeloma. (4) In 2023 the Center for International Blood and Marrow Transplant Research (CIBMTR) reported data from 214 centers documenting 10,976 patients who have undergone various form of cellular therapies. Among this cohort, 6,646 patients underwent treatment for lymphoma, and 1,401 received treatment for ALL. Since their inception, the cell therapy field has undergone significant advances, but still many challenges in terms of delivery and applicability remain. Access to CAR-T cell therapy remains limited to some populations and in this review, we aim to document obstacles for their implementation and potential solutions to overcome them.